The influence of Fatimid jurists on public life in Egypt - Al-Dhahibawi , Reem Hadi Marhaj; Ahmadi, Fatima Jan (Research Journal in Advanced Humanities, 2025)
Fatimid jurists played a major role in public life in Egypt and gained a high position within the Fatimid state. They had significant influence in managing the affairs of the populace. Due to their importance, these jurists enjoyed social support and had a substantial impact on building society and the state through their influence on economic life and their role in solving economic crises. The challenges faced by their state were not limited to the economic realm; their influence also extended to the social sphere by promoting justice and equality in Egyptian society and advocating for moral values. They stood firmly in upholding public morals, which was not limited to punishing offenders but also included shaming them. The jurists also made efforts to address people's needs, resolve disputes, and promote reconciliation among them.